Issues in Agricultural Policy and Challenge in 2014 - 황의식 (한국농촌경제연구원, 2014)
The Korean economy is expected to show a steady recovery and grow by 3.8-4.0 percent in 2014, leading to an increase in the demand for agricultural products. However, a stronger Korean won and weaker Japanese yen will make it challenging for the country to export agricultural products. The agricultural policy authorities and the entire industry need to pay keen attention to changes in macroeconomic indicators. Major policy issues will include the expansion of market opening in the agricultural sector and complementary measures in the domestic market, including issues related to Korea-China FTA and TPP negotiations. The continuous growth of the Chinese economy (with over 7.3 percent of its growth rate) and the trend of a stronger yuan will serve as an opportunity for Korea to increase the export of its products. The low income issue in rural areas is unlikely to be resolved this year due to the stagnation in growth in the agricultural industry and deteriorated conditions in the agricultural trade. Therefore, the authorities should make more efforts to expand growth engines and seek for new solutions. Although the population in rural areas will continue to naturally decrease due to a rapidly aging society, new forms of economic activities will increasingly emerge, leading to the materialization of the results of the 6th Industry Invigoration Measures. In 2014, the key policy challenges include as follows: (1) designing solutions for the low-income issue and stable management measures in rural areas in response to the expansion of market opening in the agricultural industry and natural disasters; (2) enhancing the agricultural R&D framework as a foundation for the development of technology-oriented creative agriculture to overcome a slow-growing trend in the agricultural industry; (3) laying the groundwork for eco-friendly animal husbandry to accelerate the qualitative development of the livestock industry, including the competitiveness against imported livestock products, harmonization with local agriculture, and improvement of living environment; (4) proposing a complementary measure to enhance the effectiveness of the remedy for the distribution structure of agricultural products suggested in 2013; (5) strengthening the link between the food industry and agriculture in response to the expansion of the food market, developing strategic items for the expansion of export to China through the Korea-China FTA, and establishing the foundation of production; (6) laying the groundwork for consumer policies in the agri-food sector, including the food safety management that keeps up with changes in consumer environment and support for the nutrition supply of the underprivileged; (7) nurturing rural industries and promoting the 6th Industrialization Strategy that connects production, processing, sales, and consumer experiences altogether by using both tangible and intangible resources in rural areas and expanding the links among related individuals and organizations; (8) establishing measures to enhance the quality of life in rural areas, including the 3rd Improvement Plan for Quality of Life in Rural Areas; (9) reorganizing the living zone by connecting with fostering community in rural areas; and (10) reinforcing agricultural businesses following the quantitative expansion of the Official Development Assistance (ODA) projects in the agriculture and forestry sectors, and strengthening the systematic cooperative network among related institutions.